Factors associated with anxiety and fear of falling in older adults: A rapid systematic review of reviews. - Carly Whitmore; Sarah Neil-Sztramko; Sebastien Grenier; Amy Gough; Zahra Goodarzi; Erica Weir; Iulia Niculescu; Abitha Suthakaran; Isaac Adedeji; Mahnoor Akram; Juliette Mojgani; Titus Chan; et al. (PLoS ONE)
Background Anxiety disorders are prevalent amongst older adults and negatively impact their quality-of-life and health. Anxiety disorders often go undetected or are misattributed to age-related changes. The aim of this systematic review of reviews, was to synthesize existing evidence on risk factors associated with anxiety in older adults to improve opportunities for early detection and intervention. Methods A rapid systematic review of reviews was performed. Studies were included if they were systematic reviews, specific to older adults, reported modifiable or non-modifiable factors associated with increased or decreased frequency of anxiety, and reported on anxiety disorders or symptoms of anxiety (including fear of falling). Results 27 papers met criteria for inclusion. A total of 77 unique risk and protective factors across demographic, health, environmental, and psychosocial domains were identified. Recurrently identified risk factors for anxiety included female sex, health (e.g., multimorbidity, sensory impairments), physical functions (e.g., impaired balance, history of falls), psychological factors (e.g., fear of falling, depression), social isolation, and sleep disturbances, whereas good physical health and balance confidence were protective. Conclusions This review reinforces the multifaceted and complex nature of anxiety in older adults. The results synthesized, highlight risk factors that should prompt detection of older adults for anxiety disorders and provide valuable insight for the development of tailored detection tools that better identify older adults at risk. Future research should address methodological limitations and include more diverse populations to improve opportunities for early detection and intervention in this vulnerable population.